2014
DOI: 10.1103/physreve.90.063201
|View full text |Cite
|
Sign up to set email alerts
|

Elastodynamic Green's function retrieval through single-sided Marchenko inverse scattering

Abstract: The solution of the inverse scattering problem for the one-dimensional Schrödinger equation is given by the Marchenko equation. Recently, a Marchenko-type equation has been derived for three-dimensional (3D) acoustic wave fields, whose solution has been shown to recover the Green's functions from points within the medium to its exterior, using only single-sided scattered data. Here we extend this approach to 3D vectorial wave fields that satisfy the elastodynamic wave equation and recover Green's functions fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 28 publications
0
61
0
Order By: Relevance
“…In this paper, we restrict ourselves to applications in acoustic media. Extensions of the methodology for elastodynamic wave propagation have been presented by da Costa Filho et al (2014) and .…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we restrict ourselves to applications in acoustic media. Extensions of the methodology for elastodynamic wave propagation have been presented by da Costa Filho et al (2014) and .…”
Section: Introductionmentioning
confidence: 99%
“…Research to extending the Marchenko focusing method for elastodynamic wave fields has only started recently. Da Costa et al [20][21][22] investigate an elastodynamic extension of Ref. [12] and illustrate with numerical experiments the advantages and limitations of their approach.…”
Section: Time-reversal Methodsmentioning
confidence: 99%
“…Da Costa et al [20][21][22] independently derived a similar 3D elastodynamic Marchenko scheme and illustrated it with 2D numerical examples. For a shallow focal point (situated in the second layer) several arrivals in the Green's functions are well recovered.…”
Section: Extension To 3d Inhomogeneous Mediamentioning
confidence: 99%
“…The retrieved Green's functions find valuable applications in modern seismic imaging schemes, where not only primary reflections but also internal multiples are correctly migrated Broggini et al, 2014). Extensions of the scheme have been presented for elastic media (da Costa Filho et al, 2014; and it has been shown how free-surface multiples can also be included (Singh et al, 2014). In all these cases, the multidimensional Marchenko equation is solved by iterative substitution.…”
Section: Introductionmentioning
confidence: 99%